2017
DOI: 10.1364/boe.8.003643
|View full text |Cite
|
Sign up to set email alerts
|

Quantitatively characterizing the microstructural features of breast ductal carcinoma tissues in different progression stages by Mueller matrix microscope

Abstract: Polarization imaging has been recognized as a potentially powerful technique for probing the microstructural information and optical properties of complex biological specimens. Recently, we have reported a Mueller matrix microscope by adding the polarization state generator and analyzer (PSG and PSA) to a commercial transmission-light microscope, and applied it to differentiate human liver and cervical cancerous tissues with fibrosis. In this paper, we apply the Mueller matrix microscope for quantitative detec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
57
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 109 publications
(59 citation statements)
references
References 36 publications
2
57
0
Order By: Relevance
“…Here as the examples, Figure A,B shows the imaging results of tissues from two individual CD patients, and Figure C,D shows the imaging results of tissues from two individual ITB patients. From Figure we can observe the structural features of the tissue samples as follows: (a) Compared with other elements, the m 24 , m 34 , m 42 and m 43 show some more prominent intensity distributions, which are mainly resulted from birefringence of the fibrous structures . The birefringent fibers surrounding the tuberculosis areas are induced by the inflammatory reactions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Here as the examples, Figure A,B shows the imaging results of tissues from two individual CD patients, and Figure C,D shows the imaging results of tissues from two individual ITB patients. From Figure we can observe the structural features of the tissue samples as follows: (a) Compared with other elements, the m 24 , m 34 , m 42 and m 43 show some more prominent intensity distributions, which are mainly resulted from birefringence of the fibrous structures . The birefringent fibers surrounding the tuberculosis areas are induced by the inflammatory reactions.…”
Section: Resultsmentioning
confidence: 99%
“…The Mueller matrix derived parameters of clear associations with certain structural features have been demonstrated to be potentially useful for some diagnostic purposes . For instance, we preliminarily applied the Mueller matrix microscope and MMT parameters to the pathological detections and staging of human breast duct carcinoma , liver cancer and cirrhosis , thyroid cancer , skin cancer , cervical cancer , and so on . The results showed that the microscopic Mueller matrix derived parameters are powerful indicators to describe the structural features of different pathological samples quantitatively.…”
Section: Introductionmentioning
confidence: 99%
“…Recent applications of various cancerous tissues have demonstrated the diagnostic potential of Mueller matrix-derived parameters [6,8,17,23]. However, a quantitative analysis of the Mueller matrix parameters is still needed to help select a specific group of parameters suitable for a specific biomedical polarization measurement.…”
Section: Introductionmentioning
confidence: 99%
“…The application of Mueller matrix polarization decomposition and Mueller matrix transformation in the detection of polarization in biological tissues has obtained many important research results, such as human skin basal cell carcinoma, liver cancer, cervical cancer, colon cancer, and lung cancer . However, the popularity of this method is limited by the expensive polarized light microscopy based on Mueller matrix . The 3 × 3 Mueller matrix has the advantages of simple system components and wide requirements for light sources and high efficiency .…”
Section: Introductionmentioning
confidence: 99%